PENGGUNAAN BAHAN ALAM UNTUK MENINGKATKAN KREATIVITAS SISWA MATERI TEKNIK CETAK TIMBUL KELAS II SDN LAWANGANAGUNG SUGIO LAMONGAN - Rifa Suryaningtyas; Suprayitno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
Based on observations made at SDN Lawanganagung Sugio Lamongan found obstacles Cultural Arts and Craft learning in second grade. Therefore, researchers provide solutions to plobem by using natural materials that encourage student involvement during the learning process. The purpose of this study is to discribe the activity of teachers and students during learning and describe the improvement of learning outcomes. This research uses classroom action research metodhs which are implemented in 2 cycle. The results obtained in this study are the activities of teachers Cycle 1 74,58%, Cycle 2 90,83%, student activity Cycle 1 74,37%, Cycle 2 89,37%, and creativity of student work Cycle 1 72,72%, Cycle 2 90,9%. From these can be concluded that the use of natural materials can increase the activities of teachers and students and creativity of students work.